MAKNA JUADAH PADA ACARA MANJALANG MINTUO DI NAGARI LUBUK PANDAN KABUPATEN PADANG PARIAMAN - Gustin, Nifrika Yuni; Baidar, Baidar; Elida, Elida (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
The purpose of this research was to describe the preparation, the kind of food, how to prepare, Juadah and a tool to organize the meaning contained food Juadah l brought from the commencement of the event Manjalang Mintuo in Nagari Lubuk Pandan Padang Pariaman. This type of research is qualitative research, the research area is Nagari Lubuk Pandan. The informants were Niniak Mamak, Bundo Kanduang, members of the PKK and elder parents. data collection techniques are observation, interviews, and data analysis dokumentasi.Teknik data reduction, data display, drawing conclusions and verification. The results showed that (1) The preparation phase of Juadah was to prepare the ingredients and equipment, (2) Type of food for Juadah that was Wajik, Jala Bio, Luo, Kanji, Kipang Ampiang, Kareh-Kareh (3) The tools used to compose Juadah that dulang atau papan, lapiak balambak, tali rapia dan colored paper (4) food prepared from food heavy and light at the bottom of the wajik, the Jala Bio, Aluo, the Jala Bio, starch, Kipang Ampiang and most of which are Kareh-Kareh (5) The meaning of Juadah has the meaning the bride to streng then the relationship between anak daro family and marapulai family.Keywords: Food Juadah, wedding ceremonyManjalang Mintuo, Nagari Lubuk Pandan